Osteoconductive and osseointegration properties of a commercial hydroxyapatite compared to a synthetic product (2010)
ABSTRACT: The effects of two types of hydroxylapatite on bone synthesis and properties were evaluated. An osteoconductive resorbable hydroxyapatite (OseoU), synthesized at two different temperatures of calcination (Type A and Type B) was compared with a commercial mixture of hydroxyapatite (Osteogen®), commonly used in several surgical procedures involving bone loss. The synthesis was performed in the laboratories of the University of Antioquia by precipitating a mixture of calcium nitrate and ammonium phosphate. The products obtained and the commercial hydroxyapatite were characterized by scanning electron microscopy (SEM), X- ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and energy dispersive spectroscopy (EDS). Osteoconductive and osseointegration characteristics were measured according to the products ability to induce local cell differentiation into bone forming cells. These characteristics were evaluated in hydroxyapatite implants performed in 70 New Zealand breed rabbits distributed into seven groups of 10 animals each, tested at 7, 14, 21, 28, 42, 60 and 90 days after the surgical procedure. seven groups of 10 animals each, tested at 7, 14, 21, 28, 42, 60 and 90 days after the surgical procedure. The results showed that Osteogen® and OseoU have similar characteristics in terms of crystal structure, chemical composition and adsorption properties, but morphological differences regarding particle shape. The analysis of variance found no statistically significant differences for the histopathological variables evaluated in both hydroxyapatite groups (p>0.05), indicating that the hydroxyapatites synthesized at the University of Antioquia (OseoU) had the same results as the commercial hydroxyapatite.